2019
DOI: 10.1083/jcb.201901116
|View full text |Cite
|
Sign up to set email alerts
|

Repair of nuclear ruptures requires barrier-to-autointegration factor

Abstract: Halfmann et al. describe a role for the protein BAF in nuclear envelope rupture repair. BAF recruits LEM-domain proteins and membranes to nuclear ruptures, yet surprisingly, ESCRT-III is not required to repair ruptures. These results provide new insight into the mechanisms of nuclear envelope repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
220
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(254 citation statements)
references
References 60 publications
17
220
2
Order By: Relevance
“…where it is tethered to the membrane by the LEM proteins. Such a scenario is consistent with a recently suggested model for BAF involvement in repair of mechanically induced membrane rupture (Halfmann et al, 2019). In both cases, recruitment of cytoplasmic BAF to the nuclear membrane is sensitive to changes in the mechanical properties of the nuclear membrane, and then, due to interaction with LEM proteins, BAF becomes localized to the inner nuclear membrane.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…where it is tethered to the membrane by the LEM proteins. Such a scenario is consistent with a recently suggested model for BAF involvement in repair of mechanically induced membrane rupture (Halfmann et al, 2019). In both cases, recruitment of cytoplasmic BAF to the nuclear membrane is sensitive to changes in the mechanical properties of the nuclear membrane, and then, due to interaction with LEM proteins, BAF becomes localized to the inner nuclear membrane.…”
Section: Discussionsupporting
confidence: 90%
“…Previous experiments indicated that BAF does not diffuse passively from the cytoplasm to the nucleus (Shimi et al, 2004). Furthermore, photobleaching experiments with GFP-BAF indicated that BAF-dependent repair of nuclear ruptures occurs when cytoplasmic BAF, but not internal nuclear BAF, is recruited to the ruptured sites, and this further brings LEM domain proteins that are essential for membrane sealing (Halfmann et al, 2019). These findings are consistent with a dynamic exchange between cytoplasmic and nuclear BAF, in which BAF in the cytoplasm primarily responds to mechanical signals.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is plausible that transient changes in NE organization at NE rupture sites may signal or support membrane insertion (De Vos et al, 2011;Denais et al, 2016;Raab et al, 2016;Penfield et al, 2018). For instance, BAF crosslinks chromatin at the core region of chromatin that coincides with spindle microtubules (Samwer et al, 2017) and was recently shown to accumulate at rupture sites (Halfmann et al, 2019), providing a possible mechanism to direct membrane incorporation to this region. Identifying how ER sheets are delivered into NE holes in different contexts is an important next step.…”
Section: Resultsmentioning
confidence: 99%
“…In interphase, NE ruptures that cause rapid mixing of nuclear and cytoplasmic components, and at times nuclear entry of whole organelles, depend on ESCRT-III for resealing (De vos et al, 2011;Vargas et al, 2012;Denais et al, 2016;Raab et al, 2016). Even micron-scale punctures caused by lasers undergo slow repair (Denais et al, 2016;Penfield et al, 2018;Halfmann et al, 2019). Given the evidence that the ESCRT-III spiral filament (VPS-32/Snf7/CHMP4B) resolves holes of ~30-50 nm in diameter (Wollert and Hurley, 2010;McCullough et al, 2018;Olmos et al, 2015;, mechanisms must exist to narrow large membrane holes in interphase NE ruptures and during NE reformation before ESCRT-III acts.…”
Section: Introductionmentioning
confidence: 99%